2012
DOI: 10.1016/j.physe.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Transport in three-dimensional topological insulators: Theory and experiment

Abstract: This article reviews recent theoretical and experimental work on transport due to the surface states of three-dimensional topological insulators. The theoretical focus is on longitudinal transport in the presence of an electric field, including Boltzmann transport, quantum corrections and weak localization, as well as longitudinal and Hall transport in the presence of both electric and magnetic fields and/or magnetizations. Special attention is paid to transport at finite doping, to the π-Berry phase, which le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
140
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 149 publications
3
140
0
Order By: Relevance
“…1(d)-1(g)] for x=0.10 and x=0.20 below 50K clearly indicate the changing topological character for compositions across x=0. 16. A gapped state is observed in the ARPES dispersion and momentum distribution curves for x=0.10 ( Fig.1(d,e)) whereas for x=0.20 a gapless topological Dirac surface state is clearly resolved (Fig.1(f,g)), in agreement with previous ARPES studies.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…1(d)-1(g)] for x=0.10 and x=0.20 below 50K clearly indicate the changing topological character for compositions across x=0. 16. A gapped state is observed in the ARPES dispersion and momentum distribution curves for x=0.10 ( Fig.1(d,e)) whereas for x=0.20 a gapless topological Dirac surface state is clearly resolved (Fig.1(f,g)), in agreement with previous ARPES studies.…”
supporting
confidence: 90%
“…The SdH frequency extracted from the plot of the Landau index N versus 1/B (Fig.2(c)) comes out close to 5T for x=0.19 and 2.6T for x=0.14. For x=0.19, this yields a 3D carrier density of about 6x10 16 cm -3 per valley or a total carrier density of 2.4x10 17 cm -3 for the four valleys of Pb1-xSnxSe. This also agrees with nHall≈3x10 17 cm -magnetooptical measurements on the same samples.…”
Section: Fig 2 (Color Online) (A)mentioning
confidence: 99%
“…The topological invariant is derived from the band structure properties of the bulk electrons, and in certain materials, sufficiently strong spin-orbit coupling causes the valence and conduction bands to invert, which results in the topological invariant to change and a topological surface states (TSS) to develop (see Ref. [1][2][3][4] and references therein). In the case of three dimensional (3D) TIs, such as Bi 2 Se 3 , and Bi 2 Te 3 , it was predicted and observed that the surface states span the bulk energy gap and have a linear Diraclike dispersion with chiral spin-momentum locking [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…At higher energies, however, corrections like quadratic-in-momentum and anisotropic hexagonal-warping effects should be included in the effective Hamiltonian [7]. The chiral nature of these Dirac states have some peculiar implications on their transport properties [8,9]. The back-scattering of these surface electrons from impurities, and therefore the localization is forbidden as long as the impurity potential does not break the TR symmetry [10].…”
Section: Introductionmentioning
confidence: 99%